2020
DOI: 10.1111/cdev.13369
|View full text |Cite
|
Sign up to set email alerts
|

Experience‐Driven Semantic Differentiation: Effects of a Naturalistic Experience on Within‐ and Across‐Domain Differentiation in Children

Abstract: Organized semantic networks reflecting distinctions within and across domains of knowledge are critical for higher‐level cognition. Thus, understanding how semantic structure changes with experience is a fundamental question in developmental science. This study probed changes in semantic structure in 4–6 year‐old children (N = 29) as a result of participating in an enrichment program at a local botanical garden. This study presents the first direct evidence that (a) the accumulation of experience with items in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…In this period of high brain plasticity 2 , 3 , children’s knowledge is acquired efficiently through statistical learning 4 , 5 and it is significantly shaped by interactions with the environment 6 . Despite the importance of experience on semantic knowledge (i.e., 7 ), few researches have focused on the role of school education in influencing not only how children acquire new knowledge, but also how they come to represent knowledge in long-term (semantic) memory. The organization of semantic memory plays a key role in higher cognitive functions, such as creative thinking 8 .…”
Section: Introductionmentioning
confidence: 99%
“…In this period of high brain plasticity 2 , 3 , children’s knowledge is acquired efficiently through statistical learning 4 , 5 and it is significantly shaped by interactions with the environment 6 . Despite the importance of experience on semantic knowledge (i.e., 7 ), few researches have focused on the role of school education in influencing not only how children acquire new knowledge, but also how they come to represent knowledge in long-term (semantic) memory. The organization of semantic memory plays a key role in higher cognitive functions, such as creative thinking 8 .…”
Section: Introductionmentioning
confidence: 99%
“…size confirmed that pair type was a significant predictor of the distance at which items were arranged on the screen [b = -0.18, χ 2 (1) = 45, p < 0.0001, Cohen's d = 1.44] but window size was not [b = -0.000002, χ 2 (1) = 0.002, p = 0.97]; the model included by-participant random intercepts and slopes for the effect of pair type. The effect size of the effect of pair type was of similar (albeit larger) magnitude relative to when data were collected in person (Vales et al, 2020a).…”
Section: Resultsmentioning
confidence: 60%
“…The sample in this study was a convenience sample resulting from an ongoing partnership with the science outreach team at a local botanical garden, and thus we did not aim to obtain a geographically diverse sample (although some families joined from out-of-state, which would have been unlikely had the programs taken place in person). When planning this collaboration, we took steps to increase diversity in the demographics of children participants, both through publicizing the camps in underserved neighborhoods and by reducing enrollment costs -and these efforts seem to have been successful to some extent, as we saw an increase in nonwhite participants relative to a prior collaboration (Vales et al, 2020a) and considerable variability in the neighborhoods (i.e., zip codes) where the participants lived. However, because these camps were moved to a remote medium as a result of socialdistancing guidelines due to the COVID-19 pandemic in the Spring and Summer of 2020, there were considerable changes in enrollment as family and childcare circumstances quickly changed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations